Association Between Cardiovascular Disease Risk Factors and Rotator Cuff Tendinopathy: A Cross-Sectional Study. Issue 2 (February 2017) - Applegate, Kara Arnold; Thiese, Matthew S.; Merryweather, Andrew S.; Kapellusch, Jay; Drury, David L.; Wood, Eric; Kendall, Richard; Foster, James; Garg, Arun; Hegmann, Kurt T.
Abstract : Objective: Recent evidence has found potential associations between cardiovascular disease (CVD) risk factors and common musculoskeletal disorders. We evaluated possible associations between risk factors and both glenohumeral joint pain and rotator cuff tendinopathy. Methods: Data from WISTAH hand study participants ( n = 1226) were assessed for associations between Framingham Heart Study CVD risk factors and both health outcomes. Results: A strong association was observed between CVD risk scores and both glenohumeral joint pain and rotator cuff tendinopathy. Peak odds ratios (ORs) of the adjusted models were 4.55 [95% confidence interval (95% CI) 1.97 to 10.31] and 5.97 (95% CI 2.12 to 16.83), respectively. The results show a dose–response trend of increasing risk. Conclusions: Individual risk factors were associated with both outcomes. Combined, CVD risk factors demonstrated a strong correlation with glenohumeral joint pain and an even stronger correlation with rotator cuff tendinopathy. Results suggest a potentially modifiable disease mechanism.